Multi-Agent Systems for E-Commerce - Solodukha, Tatiana V.; Sosnovskiy, Oleg A.; Zhelezko, Boris A. (Systemy wieloagentowe w handlu elektronicznym, 2010)
The article focuses on multi-agent systems and domains that can benefit from multiagent technology. In the last few years, the agent based modelling community has developed several practical agent based modelling toolkits that enable individuals to develop agent-based applications. The comparison of agent-based modelling toolkits is given. Multi-agent systems are designed to handle changing and dynamic business processes. Any organization with complex and distributed business processes can benefit from multi-agent technology. The model of the e-commerce platform targeted at online trading and auction systems, e-markets and private trading exchanges is presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 131-140
Keywords: agent; multi-agent systems; e-commerce; agent-based modelling